Molecular Mechanism of Apoptotic Cell Death in Cyanidin-3-glucoside-induced Cytotoxic Potential on Human Liver Carcinoma (HepG2) Cell Line - Suresh Mickymaray
Background: Liver cancer is one of the most prevalent cancers around the world and the leading cause of cancer-related deaths. Because liver cancer prevalence has increased significantly, there are no established therapies, and there are serious adverse reactions associated with the use of medications already available, new and more potent anticancer agents must be investigated. Aim: Using in vitro methods, we have assessed Cyanidin-3-glucoside (C3gc)'s anticancer activities and the underlying molecular mechanisms. Materials and Methods: In the current investigation, the cytotoxicity and apoptotic activity of C3gc against liver cancer cell line HepG2, has been investigated using MTT assay, LDH release assay, AO/EtBr dual staining, DAPI staining, ROS estimation, Mitochondrial ATPase assay, and oxidative stress parameters has been examined. Results: Assays of MTT and LDH release showed that C3gc exhibited cytotoxic potential and cell membrane distribution by reducing cell viability dose-dependently. The AO/EB and DAPI staining techniques were used to assess morphological changes associated with apoptosis, confirming its apoptotic nature. In HepG2 cell lines, C3gc increased ROS generation and ATPase activity. Furthermore, C3gc-treated cells showed a significant increase in MDA levels while decreasing SOD and GSH levels. This reflects increased oxidative stress and decreased antioxidant activity in HepG2 cells. Conclusion: C3gc inhibits cancer cell proliferation by enhancing ROS levels, disrupting cell membrane integrity, and causing DNA fragmentation and apoptosis through oxidative stress-mediated pathways. Thus, C3gc could be effectively utilized as an effective anti-cancer alternative for liver cancer.